A Comprehensive Analysis on Abundance, Distribution, and Bionomics of Potential Malaria Vectors in Mannar District of Sri Lanka - Gunathilaka, Nayana (Malar Res Treat, 2019)
BACKGROUND: A detailed knowledge of the distribution of the malaria vectors in Mannar district of Sri Lanka has not been studied after 1927. Past records indicated the presence of only seven species of anophelines, namely, An. culicifacies, An. subpictus, An. barbirostris, An. peditaeniatus, An. nigerrimus, An. Jamesii, and An. maculatus. There have been many changes in terms of distribution of Anopheles in the district over time. METHODS: Entomological surveillance was conducted on a monthly basis, comprising indoor hand collection, window trap collection, cattle-baited net collection, cattle-baited hut collection, and larval survey from June 2010 to June 2012 in 12 study areas under three entomological sentinel sites. The relationship between seven abiotic variables of the breeding habitats was measured. Pearson's correlation coefficients were used to determine the associations between climatic variables and anopheline densities. RESULTS: A total of 74,181 mosquitoes belonging to 14 Anopheles species were recorded. An. subpictus was the most predominant species from all techniques representing 92% (n=68,268) of the total anopheline collection. However, Anopheles culicifacies was not recorded from any site during the study period. Larval surveys identified 12 breeding habitat categories including waste water collections, lagoon water collections, and drains which were not recorded as breeding habitats by previous studies. The mean dissolved oxygen level of waste water collections was 3.45±0.15 mg/l. The mean salinity and conductivity of lagoon water collections were 21105±1344 mg/l and 34734±1974 μs/cm, respectively. CONCLUSION: The present study provides the updated knowledge on anopheline distribution and vector bionomics. Therefore, documentation of the current knowledge would be useful for learners and health authorities to design appropriate vector control measures in the prevention of reintroduction of malaria.